Methods in the in vitro multiplication of 'Pacovan' banana (Musa spp.) (Research, Society and Development, 2021)
The cultivation of 'Pacovan' banana is still carried out using traditional methods in the state of Amazonas, where there are still records of fruit production with diseases caused by fungi and bacteria. However, other propagation methods, such as in vitro micropropagation, can be developed and improved, so that the multiplication rate can be increased in a short period of time, in addition to significantly improving the quality rate of seedling production. However, contamination rates are still one of the biggest problems with this technique. This work aimed to evaluate the improvement in the asepsis process by analyzing different types of concentrations of alcohol, sodium hypochlorite and Tween 20 and different time variations during the asepsis process of the meristematic explant, in order to identify the most efficient decontamination process. The experiment was planned in a completely randomized experimental design for linear regression analysis, where they were constituted by three treatments and twenty repetitions, with each repetition represented by five explants in different experiments. Data were subjected to analysis of variance (ANOVA), followed by Tukey 5% probability mean tests. The results allowed us to conclude that, with a long explant time submerged in sodium hypochlorite, there is efficacy against fungi and bacteria. However, high concentrations of NaClO lead to toxicity due to high oxidation. As it is an oxidizing agent, high concentrations become toxic to explants. In the experiments, the lowest level of contamination of the treatments tested was E3, allowing the normal development of the explants and allowing it to be used to control contamination in the micropropagation of 'Pacovan' banana in vitro.